Mekanisme Koping pada Odha dengan Pendekatan Teori Adaptasi Callista Roy - Sandu Siyoto; Yuly Peristiowati; Eva Agustin (Jurnal Ners, 2016)
Introduction: The negative impact caused by people living with HIV/AIDS is a matter of physical, psychosocial and emotional, so that people living with HIV need to improve towards adaptive coping mechanisms. Roy explained that there are three stimulus that can influence the coping mechanisms, there are stimulus focal, contextual stimulus, stimulus residual. The purpose of this study was to determine the factors related with coping mechanisms based on the Roy Adaptation Theory.Methods: The study design using analytic correlational cross-sectional approach, 30 respondents were selected by purposive sampling technique. The research instrument used questionnaire.Results: The results showed focal stimulus, stimulus contextual, adan residual stimulus associated with coping mechanisms in people living with HIV, the majority of respondents have a negative coping mechanisms as many as 18 respondents (60.0%) and positive coping mechanisms as much as 12 respondents (40.0%).Discussion: Based on the analysis showed there is relationship stimulus focal p-value = 0.018 and contextual stimulus p-value = 0.004, while the residual stimulus doesn’t have relation with the coping mechanisms of people living with HIV in KDS friendship plus Kediri. During join the peer support groups people with HIV has a place to share the feelings and emotions and be able to communicate social well, so that their focal and contextual stimuli can stimulate a response from KDS cognator and regulators that can affect physiological functions so they can adapt adaptively.